Comparative study of specificity and activity of allergens prepared from brucella by different methody (Experimental biology, 2015)
In article was shown of data on studying of comparative activity and specificity of the allergens prepared by different methods from different types of brucellas. It was shown that the most expressed sensibilizing properties for sea pigs Brucella melitensis Rev-1, in comparison with Brucella abortus 19 possess. It is revealed that the greatest allergenic activity is found in under sediment part after sedimentation the big dispersed of connections with the help of an izoionofocusing. In experiences on sea pigs it is shown that the allergen received by disintegration of brucellas by energy of ultrasonic waves, shows the expressed activity at intracutaneous introduction it in cultivation till 1:15. Thus, the received preparation can be applied to allergic diagnostics of a brucellosis in 10 multiple cultivation
Keywords: brucellosis; brucella; reaction of agglutination; reaction of bining of compliments; allergy samples; allergens